Adaptive channel allocation for spectrum sharing based on ACO algorithm. (29th October 2021) - Priya, J. Suji; Padma, T.
The customer requirements increase day by day, so the radio spectrum demand also increases. The situation is far worse if data usage is getting higher. The spectrum sharing techniques are designed in the cognitive radio (CR) system, which increases the efficiency of spectrum usage through the sharing process overcomes these issues. Even though several spectrum-sharing techniques are available in the literature, new methods are required for different applications. The methods vary from the mode of operation, interference management, and application used. This paper presents the implementation of spectrum sensing and sharing techniques.